A new geometric combination of cutting and bleeding modules for surgical simulation systems. (July 2021) - Shi, Wen; Gao, Xin; Lv, Lei; Pan, Zhuo; Shao, Jing
Highlights: A new geometric combination of cutting and bleeding modules is introduced in surgical simulation. Volume rendering and the multidimensional parameters are used to describe the internal structure. The haptic interaction calculation transmits the unique hardness and toughness of each part to the operator. Different rendering algorithms are used for flowing and gushing blood correspondingly to achieve realistic bleeding states. Geometric connection between cutting and bleeding modules is realized by multidimensional parameters. Abstract: Background and objectives: Cutting and bleeding are often independent of each other in the traditional virtual surgery system because of the differences in the calculation of physical models and the lack of internal structure. In order to improve the fidelity of virtual surgery scene and the training value for surgeons, a new geometric combination of cutting and bleeding modules is introduced. Methods: In this paper, we introduce a cutting model based on volume rendering and meshless method. The multidimensional parameters derived from the gray values are presented to participate in the calculation of both physical and geometric models, which distinguishes between different adjacent soft tissues. The bleeding simulation with improved physical properties and rendering algorithms of geometric model is proposed to meet several different bleeding states. After cutting procedures, the tearing parts can be judged through the vision and the tactile sensation. The initial velocity and rendering algorithm of bleeding particles are determined by the multidimensional parameters of the cutting position, which realizes the geometric combination of cutting and bleeding modules. Results and conclusions: Simulation results show that tearing different tissue structures will produce corresponding bleeding states. When the skin and flesh are torn, the blood is slowly generated at the incision, and then diffuses to the surface of soft tissue. When the important blood vessels are ruptured, the blood gushes from the laceration. Compared with the conventional virtual surgery system, both visual effect and interactivity of the cutting and bleeding modules are improved in the proposed geometric combination.